2020
DOI: 10.1002/lio2.477
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and risk of sudden sensorineural hearing loss: A systematic review and meta‐analysis

Abstract: Objective: The pathophysiology of idiopathic sudden sensorineural hearing loss (SSNHL) is poorly understood. This study aimed to explore the association of migraine and risk of SSNHL in a meta-analysis of population-based cohort studies. Methods: A systematic literature search of studies published until December 2019 was carried out in Medline, Embase, Scopus, Web of Science, and Google Scholar using appropriate keywords. References of the retrieved articles were also examined for inclusion. Random-effects met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Migraine was associated with a 1.8-fold increased risk of developing ISSNHL, exploring the possibility of a vascular etiology in ISSNHL. 43 On the other hand, recent works indicated that ISSNHL may be an independent risk factor for the development of stroke, especially in elderly patients. 13 Vascular mechanisms in acute unilateral peripheral vestibulopathy were also proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine was associated with a 1.8-fold increased risk of developing ISSNHL, exploring the possibility of a vascular etiology in ISSNHL. 43 On the other hand, recent works indicated that ISSNHL may be an independent risk factor for the development of stroke, especially in elderly patients. 13 Vascular mechanisms in acute unilateral peripheral vestibulopathy were also proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the association between migraine and ISSNHL was analyzed in one meta‐analysis. Migraine was associated with a 1.8‐fold increased risk of developing ISSNHL, exploring the possibility of a vascular etiology in ISSNHL 43 . On the other hand, recent works indicated that ISSNHL may be an independent risk factor for the development of stroke, especially in elderly patients 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, up to 81% of patients with migraine reported phonophobia, in comparison with only 12.1% of patients with a non-migrainous headache, and the combination of phonophobia and hearing loss was reported by some patients [ 28 ]. A recent meta-analysis showed that migraineurs may have a higher risk of developing sensorineural hearing loss [ 153 ]; therefore, the exclusion of migraine patients with hearing loss from the majority of the trials may lead to biased conclusions. In 1985, Blau and Solomon reported noise as a migraine trigger in 4/50 patients with migraine [ 133 ] and the potential measurability of phonophobia was suggested.…”
Section: Neuro-otological Manifestationsmentioning
confidence: 99%
“…Except for left-handedness (45), associations were found between migraine and the increased risk of phosphene (36), RLS (37), epilepsy (38), infant colic (40), suicidal contemplations (41), SSNHL (18), asthma (42), depression ( 43), primary open angle glaucoma (POAG) ( 44), together with attentiondeficit/hyperactivity disorder (ADHD) (46). One meta-analysis reported a statistically significant inverse association between migraine and total breast cancer risk (39).…”
Section: Other Medical Conditionsmentioning
confidence: 99%
“…This might be explained by a number of plausible mechanisms, such as endothelial dysfunction, cerebral hypoperfusion, systemic vasculopathy, and a hypercoagulable state (10)(11)(12)(13). Recently, emerging body of evidence from scientific literature reported the associations between migraine and other diseases, including restless leg syndrome (RLS) (14), diabetes (15), irritable bowel syndrome (IBS) (16), retinal nerve fiber layer (RNFL) thickness reduction (17), sudden sensorineural hearing loss (SSNHL) (18), major depression, and panic disorder (19). However, the published studies focused on a single health-related outcome.…”
Section: Introductionmentioning
confidence: 99%